Mutual Interplay of Host Immune System and Gut Microbiota in the Immunopathology of Atherosclerosis - Yeh, Chih-Fan (Int J Mol Sci, 2020)
Inflammation is the key for the initiation and progression of atherosclerosis. Accumulating evidence has revealed that an altered gut microbiome (dysbiosis) triggers both local and systemic inflammation to cause chronic inflammatory diseases, including atherosclerosis. There have been some microbiome-relevant pro-inflammatory mechanisms proposed to link the relationships between dysbiosis and atherosclerosis such as gut permeability disruption, trigger of innate immunity from lipopolysaccharide (LPS), and generation of proatherogenic metabolites, such as trimethylamine N-oxide (TMAO). Meanwhile, immune responses, such as inflammasome activation and cytokine production, could reshape both composition and function of the microbiota. In fact, the immune system delicately modulates the interplay between microbiota and atherogenesis. Recent clinical trials have suggested the potential of immunomodulation as a treatment strategy of atherosclerosis. Here in this review, we present current knowledge regarding to the roles of microbiota in contributing atherosclerotic pathogenesis and highlight translational perspectives by discussing the mutual interplay between microbiota and immune system on atherogenesis.